Comparison between Measurements of Clinical Attachment Level and Transgingival Probing with Alveolar Bone Crest Level in Chronic Periodontitis Patients - Sah, Sunita; Shrestha, Sajeev; Acharya, Pujan; Adhikari, Khushbu (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Periodontitis is an inflammatory disease of the supporting tissues of the teeth that leads to crucial changes in the bony architecture. Early detection is of great practical significance so that treatment may be administered before irreversible destruction could occur. Differences exist between different diagnostic methodology concerning the relationship between the measurements and the level of the lesion. The aim of this study was to assess relationship between clinical attachment level (CAL) and alveolar bone crest level (ABCL), reliability of transgingival bone probing level (TBL) for ABCL measurement, and clinical biologic width (CBW) measurement in chronic periodontitis patients. Methods: An analytical cross-sectional study was conducted on 238 periodontal sites in 25 chronic periodontitis patients, aged 20–60 years who were planned for periodontal flap on residual pocket depth of 5-8mm after four weeks of non-surgical therapy. Stent was used for coronal fixed reference point. The relative attachment level (RAL), relative transgingival bone probing level (RTBL), relative alveolar bone crest level (RABCL), and CBW were measured at six sites per tooth excluding third molars. Descriptive and inferential statistical analysis was done. Probability of significance (p-value) was set at 5%. Results: Overall RAL, RTBL and RABCL (mean ± SD) were 8.08 ± 1.23, 10.82 ± 1.1, and 11.15 ± 1.36 mm respectively. Overall CBW (mean ± SD) was 3.06 ± 0.634 mm. Conclusions: There was a significant positive correlation of CAL and TBL with ABCL. Also, the CBW was greater than that of standard histologic BW.